Como o uso das redes sociais mudou o engajamento de torcedores de futebol no Brasil - Feitosa, Anselmo Penha (2019)
The digital era has introduced technologies in communication market, being either on behalf of companies as it is of their clients. On one side, there are institutions and interfaces which enable them to convey their messages directly to their audience and, on the other side, people who value personalization, are active towards their consumption and participate spontaneously on the online debate. Internet is a means of communication which has grown in digital era. The social networks in it enable interaction between their users, either pages or personal profiles. Soccer teams, identified as brands, have these interfaces so as to communicate with no intermediary. The end of this as something necessary gives teams participating in Soccer Brazilian Championship – Stage D, an opportunity to engage them in their products and services offered. This research has the proposal of identifying how these teams behave on Facebook social network. From this, using bibliography towards technology, communication and marketing to present strategies used by those which, in 2018, had already started using this tool. The analysis consists of data from pages Ferroviária de Araraquara, Associação Ferroviária de Araraquara’s official one; Clube Atlético Linense, owned by homonym soccer team; and Mirassol Futebol Clube, which also carries its team’s name. All three teams participated in Stage D 2018 and their pages are presented on this research so as to make understanding the way social networks changed engagement for Brazilian soccer teams. The total amount of 251 posts is described on three chapters and their characteristics were mapped and categorized as patterns identified